Effects of dietary vitamin E on antioxidant defence mechanisms of juvenile turbot (Scophthalmus maximus L.), halibut (Hippoglossus hippoglossus L.) and sea bream (Sparus aurata L.) - Tocher, D.R.; Mourente, G.; Van der Eecken, A.; Evjemo, J.O.; Diaz, E.; Bell, J.G.; Geurden, Inge; Lavens, P.; Olsen, Y. (HAL CCSD, 2002)
International audience